The effect of cultural and institutional factors on initiation, completion, and duration of cross-border acquisitions - Lawrence, Edward R.; Raithatha, Mehul; Rodriguez, Ivan (Journal of Corporate Finance, 2021)
We study the effect of cultural and institutional distances on the probability that a firm from an acquiring country announces an acquisition of a firm in a target country (initiation), the probability that an announced deal is completed (completion), and the average time it takes to complete an acquisition (duration). We find that culture plays a decisive role in deal initiation. Completion and duration of a deal is largely unaffected by the cross country cultural and institutional differences and depends on deal level characteristics. We find a higher probability for acquirers to hire Top-tier advisors when they initiate deals in countries with higher cultural differences. We also find that use of Top-tier advisors by acquirers increases the probability of completion of the deal.